A comparative study of C-reactive protein levels in patients with major depressive disorder with and without suicidal attempts - Seetharaman, Arun; Suresh, Keerthana; Thirumal, Ramkumar; Radhakrishnan, Sriramadesigan (Rzeszów University Press, 2026)
Introduction and aim. Major depressive disorder (MDD) is closely linked to suicidal behavior, and systemic inflammation ‒ particularly elevated C-reactive protein (CRP) ‒ has been proposed as a contributing factor. However, evidence comparing CRP patterns separately in suicide attempters and non-attempters remains limited, especially in underrepresented populations. The aim of this study was to compare serum CRP levels in patients with MDD with and without a history of suicide attempts. Material and methods. This cross-sectional analytical study included 60 adults diagnosed with MDD according to ICD-10 criteria. Participants were divided into two groups: those with a history of suicide attempts (n=30) and those without such a history (n=30). Depression severity was assessed using the Hamilton Depression Rating Scale (HAM-D). Serum CRP levels were measured using a turbidimetric method. Statistical analyses included Student’s t-test, Mann-Whitney U-test, and Pearson’s correlation. Results. CRP levels were significantly higher among suicide attempters compared with non-attempters (4.47±3.53 mg/L vs 2.50±3.59 mg/L; p=0.03). A significant positive correlation between HAM-D scores and CRP levels was observed in the suicide-attempt group (R=0.52; p=0.003), whereas no such correlation was found in non-attempters (R=0.12; p=0.52). Severe depression was more common among suicide attempters (30/44 cases). Conclusion. This study provides novel evidence that the association between inflammation and depressive symptom severity is present only in patients with a history of suicidal behavior. Elevated CRP may therefore represent a potential marker for identifying MDD patients at increased risk of suicide.
The ethical approval was acquired from the institutional ethical committee of Sri Lakshmi Narayana Institute of Medical Sciences” IEC/C-P/13/2022.
Keywords: C-reactive protein; depressive patients; major depressive disorder; pro-inflammatory marker; suicidal behavior